Coumarin-based fluorescent 'AND' logic gate probes for the detection of homocysteine and a chosen biological analyte. Issue 45 (27th August 2019) - Wu, Luling; Gardiner, Jordan E.; Kumawat, Lokesh K.; Han, Hai-Hao; Guo, Ruiying; Li, Xin; He, Xiao-Peng; Elmes, Robert B. P.; Sedgwick, Adam C.; Bull, Steven D.; James, Tony D.
Abstract : With this research we set out to develop of a number of coumarin-based 'AND' logic fluorescence probes that were capable of detecting a chosen analyte in the presence of HCys. Abstract : With this research we set out to develop a number of coumarin-based 'AND' logic fluorescence probes that were capable of detecting a chosen analyte in the presence of HCys. ProbeJEG-CAB was constructed by attaching the ONOO − reactive unit, benzyl boronate ester, to a HCys/Cys reactive fluorescent probe, CAH . Similarly, the core unitCAH was functionalised with the nitroreductase (NTR) reactive p -nitrobenzyl unit to produce probeJEG-CAN . Both, JEG-CAB andJEG-CAN exhibited a significant fluorescence increase when exposed to either HCys and ONOO − (JEG-CAB ) or HCys and NTR (JEG-CAN ) thus demonstrating their effectiveness to function as AND logic gates for HCys and a chosen analyte.